Microbiological effect of topically applied Weissella cibaria on equine pastern dermatitis - Styková, Eva; Valocký, Igor; Kačírová, Jana; Fecskeová, Lívia Kolesár (Frontiers in Veterinary Science, 2025)
Equine pastern dermatitis (EPD) is a multifactorial disease with a change in the skin microbiome. The present study monitored the influence of Weissella cibaria Biocenol™ 4/8 D37 CCM 9015 stabilized on alginite on the skin microbiota of healthy horses and model patients with EPD. Based on clinical signs, EPD lesions were identified as exudative or proliferative forms. A comparison of the initial microbial community based on 16S rRNA amplicon sequencing revealed that there was a statistically significant difference between healthy vs. exudative (R = 0.52, p = 0.003) and exudative vs. proliferative communities (R = 0.78, p = 0.043). The healthy skin microbiota was dominated by the families Corynebacteriaceae (19.7 ± 15.8%) and Staphylococcaceae (15.8 ± 10.7%). Streptococcus (11.7 ± 4.1%) was the dominant genus in the exudative group together with Corynebacterium (11.0 ± 3.8%), while Staphylococcus (15.6 ± 14.5%) dominated the proliferative group. The genus Staphylococcus represented only 0.5% of the exudative skin microbial community, a major difference between EPD-affected lesion types. Upon application, there was a statistically significant shift in community composition in all the groups, including the healthy community; however, the change was the most significant in the exudative community. On average, the genus Weissella represented 80.0 ± 13.3% of the exudative and 49.0 ± 30.0% of the proliferative bacterial community during treatment. One week after the application period, richness and diversity increased and were comparable in all groups. The application of the W. cibaria strain was associated with a significant decrease of the genera Staphylococcus, Moraxella, and Rothia in the proliferative group and with a decrease of Streptococcus and Clostridium in both exudative and proliferative groups. Based on our results, we conclude that a topically applied W. cibaria RIFR, stabilized on alginit, induced potentially beneficial shifts in the composition of the skin microbiota.